Pengaruh Penerapan Model Pembelajaran Time Token dengan Menggunakan Media Kartu Indeks Terhadap Hasil Belajar Biologi Siswa Kelas XI IPA SMA Negeri 1 Cina Kabupaten - Musyafar, . (bionature, 2010)
This research is a queasy experiment that aim is to know the influence of using time token learning model by using index cards as a media to the result of student biology learning at XI grade students of SMA Negeri 1 Cina. The subjects of this research are the students at XI IPA1 as the experiment class and the students at XI IPA2 as control class, with the total number of each class are 30 students for experiment class and 32 students for control class. The experiment has done at both classes for 8 hours meeting (3 times for giving materials and 1 time for evaluation). The data collection has done to evaluate learning result by using written test. The collected data were analyzed by using descriptive statistic analysis and inferential analysis. The research result shows (a) from descriptive analysis result, the mean score experiment class result is 77,77 while the control class mean is 63,64. (b) From inferential analysis by using correctness t0,05 shows ttest =5, 24 and ttable = 2,00 so it describe that ttest is higher than ttable. By this experiment result, the researcher concludes that there is an improvement in student’ biology learning result by using time token learning model which uses index card as a media at IX class of SMA Negeri 1 Cina, because experiment class learning result is higher than control class learning result.